Insights from computational exploration of bioactive compounds of combretum indicum targeting TGF-b1 to treat wound healing: Molecular docking and DFT approaches - Forid, Md Shaekh; Dubey, Amit; Roney, Miah; Tufail, Aisha; Huq, A. K. M. Moyeenul; Mohd Hamzah, Mohd Nasir; Mohd Fadhlizil Fasihi, Mohd Aluwi; Muhammad Saupi, Azuri; Wan Maznah, Wan Ishak (Malaysian Society for Biochemistry & Molecular Biology (MSBMB), 2025)
Transforming growth factor-beta type-1 (TGF-β1), a protein that is a druggable target for inflammation, has been identified to be associated with wound healing. Dysregulation of the wound-healing process can result in the development of chronic ulcers or excessive inflammation. Despite the availability of the TGF-β1 inhibitor drug, there is an urgent requirement for additional therapeutic treatment options to effectively manage wound healing in the expanding global population. In this study, the molecular docking and Density-Functional Theory (DFT) approach were used to discover wound healing agents that can target TGF-β1. Seventeen compounds detected via UPLC-Q-TOF/MS analysis of Combretum indicum were selected from our previous report to obtain the hit compound(s) that exhibit inhibition of TGF-β1. The molecular docking findings revealed that actinidioionoside (-56.2999 kcal/ mol) binding affinity is stronger than the studied compound as well as the co-crystal ligand (-43.016 kcal/ mol), indicating a potentially more substantial interaction with the target. Moreover, actinidioionoside interacted with four amino acid residues, namely, Ly337, Lys232, Asp351, and Leu278, while a co-crystal ligand interacted with His283, which formed a hydrogen bond. Furthermore, DFT and Molecular Electrostatic Potential (MESP) findings emerged as the most promising hit with all the above favorable properties of actinidioionoside. Based on the results, it can be concluded that actinidioionoside is a promising prospective agent against TGF-β1 for regulating wound healing. However, further in vitro and in vivo research on C.indicum are needed.